1966
DOI: 10.1111/j.1751-1097.1966.tb05952.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies to Interpret ‘High‐energy Phenomena’ of Photomorphogenesisl on the Basis of Phytochrome

Abstract: Abstract— Kinetic studies with the mustard seedling (Sinapis alba L.) support the hypothesis that the so‐called ‘high energy reaction’ of photomorphogenesis can be understood solely on the basis of phytochrome. Light‐induced anthocyanin synthesis (a typical ‘positive’ photoresponse(1) and light dependent inhibition of hypocotyl lengthening (a typical ‘negative’ photoresponse(1)) have been investigated. In order to explain the experimental data we have to assume that there are two different types of phytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
39
1
1

Year Published

1967
1967
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 9 publications
4
39
1
1
Order By: Relevance
“…One is the low energy, R -FR' reversible phytochrome system (1, 8,12,15,17,18,28,40,44) and the other is the high energy reaction, also called high irradiance reaction system of plant photomorphogenesis (4,9,10,14,15,28,44 (4,14,28,29,37,41,44 germination (11, 14, 22, 23, 42, 45). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One is the low energy, R -FR' reversible phytochrome system (1, 8,12,15,17,18,28,40,44) and the other is the high energy reaction, also called high irradiance reaction system of plant photomorphogenesis (4,9,10,14,15,28,44 (4,14,28,29,37,41,44 germination (11, 14, 22, 23, 42, 45). …”
mentioning
confidence: 99%
“…Studies of light-dependent anthocyanin synthesis and of other plant photomorphogenic responses have shown that two photoprocesses are operating (8- 10,15,17,18,24,27,35,36,39,40,44). One is the low energy, R -FR' reversible phytochrome system (1,8,12,15,17,18,28,40,44) and the other is the high energy reaction, also called high irradiance reaction system of plant photomorphogenesis (4,9,10,14,15,28,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences have been found in the wavelengths of the peaks of action and in the combinations and relative efficiencies of the effective spectral regions (1-3, 6, 7, 9, 13-16). As an example, consider the differences in the spectral sensitivity of anthocyanin synthesis in young seedlings: BL2 is the only effective region in sorghum (2); BL and FR are about equally effective in mustard (17); FR is more effective than BL in turnip (13); and BL is more effective than FR in tomato (11). The causes of these differences are still poorly understood and are partly responsible for the state of uncertainty about the nature of the HIR photoreceptor (9,15).…”
mentioning
confidence: 99%
“…(b) Complete data for the dose response curves and for the time course of the responses under irradiation with different spectral regions are not always available. (c) There are some data which show that the spectral sensitivity of some HIR responses can be markedly affected by the irradiance and duration of the exposure and by the age of the system (3,11,17). When these points are taken into consideration, it becomes rather difficult to establish the real significance of the differences in the spectral sensitivity of different HIR responses.…”
mentioning
confidence: 99%